2010
DOI: 10.1037/a0020313
|View full text |Cite
|
Sign up to set email alerts
|

History of peer victimization and children's response to school bullying.

Abstract: We examined the degree to which children with and without a history of stable peer victimization differentially endorse strategies for dealing with school bullies. Participants were 323 children, 58 of whom met criteria for chronic peer victimization. Children with a history of stable peer victimization differed from comparison children in how they rated various strategies, but the findings were gender specific. Chronically bullied girls were less inclined to endorse any strategy (coercive or noncoercive), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 53 publications
4
41
1
Order By: Relevance
“…Elledge et al, 2010;Hampel et al, 2009;Kochenderfer-Ladd, 2004). Still, when we evaluate the results, we have to remember the limits of the study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Elledge et al, 2010;Hampel et al, 2009;Kochenderfer-Ladd, 2004). Still, when we evaluate the results, we have to remember the limits of the study.…”
Section: Discussionmentioning
confidence: 96%
“…In general, active responses are found to prevent aggression, while passive and an aggressive response maintains aggression (KochenderferLadd & Pelletier, 2008;Wilton, Craig, & Pepler, 2000). Victims of bullying employ various coping strategies such as verbal confrontation, revenge-seeking behaviour, solicitation of advice and support from adults or friends, conflict resolution, avoidance, distraction, humorous response, rumination and ignoring (Elledge et al, 2010;Hampel, Manhal, & Hayer, 2009;Kochenderfer-Ladd, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The Coping with Bullying questionnaire may also serve as a useful tool for skilled professionals working with students in their own settings to assess students' coping strategies as part of a well-considered school program; one that also strategically addresses individual students' social and emotional wellbeing and mental health issues as psychosocial problems and ineffective coping are complexly connected (Elledge et al, 2010;Singh & Bussey, 2010;Visconti & Troop-Gordon, 2010). In the words of one of the informed professionals: 'The effectiveness of strategies depends on skills that a student has and/or the skills that the people from which a student seeks advice have.…”
Section: Implications For Research Policy and Practicementioning
confidence: 99%
“…There are few studies addressing selective interventions directed to victims of bullying [32]. A study developed in English schools identified that the training of social skills improved the self-esteem of children, though victimization was not significantly reduced [18].…”
Section: Introductionmentioning
confidence: 99%